INFLUÊNCIA DA GOVERNANÇA CORPORATIVA NA PRÁTICA DE GERENCIAMENTO DE RESULTADOS - KAWAI, RICARDO MAKOTO (2017)
This study aimed to investigate the influence of corporate governance and three of its internal mechanisms: board of directors, concentration of ownership control and identity of the controlling shareholder, on the management of results in Brazilian listed companies, listed on BM&FBOVESPA. Results quality variables derived from the discretionary accruals determined by two models used as proxy for results management: Kang and Sivaramakrishnan (1995) and McNichols (2002), from 2009 to 2015. As proxy of corporate governance was the corporate governance index prepared by Leal, Carvalhal and Ievorlino (2015) adopted for the year 2015. The comparison between two groups made through non-parametric tests indicating a non-significant relationship between corporate governance and results management, which do not support the theory that corporate governance inhibits results management. In order to verify the relationship between the internal mechanisms of corporate governance and results management, multiple linear regressions using the Ordinary Least Squares (OLS) method. In which independent variables: board of directors, control concentration and controller identity; Together with the control variables: return on assets, leverage and company size did not present a statistically significant relationship with the corporate governance dependent variable. There was a negative relationship between company size and results management in both models and the variable return on assets presented a negative relation with the McNichols model. The study suggests that the internal mechanisms of corporate governance are not sufficient to inhibit the management of results measured by models that detect them through discretionary accruals.